Thermal and magnetic properties of Ni51Mn28.5Ga19.5B magnetic-shape-memory alloy - Kok, M.; Yakinci, Z. D.; Aydogdu, A.; Aydogdu, Y. (Springer, 2014)
Ni51Mn28.5Ga19.5B magnetic shape-memory alloy was produced in Arc melter under vacuum. The crystal structure of the produced alloy was determined by using XRD. The XRD analysis results indicated the presence of two phases; namely the martensitic phase that the alloy was determined to display non-modulated martensitic phase and the gamma phase characteristics. DSC was used to determine the transformation temperature, the thermodynamic quantities of martensitic transformation and the activation energy in the Ni51Mn28.5Ga19.5B alloy. The austenite transformation temperature and activation energy of transition were found as 46.92 A degrees C and 303.12 kJ mol(-1) respectively. The 1 % presence of the boron element in the alloy was observed to play a significant role in the transition temperature as indicated by the comparison of the values obtained in this study with those available in the literature. The magnetic properties of this alloy were determined using the PPMS instrument. The magnetic saturation value was determined as 66 emu g(-1).
Keywords: Magnetic materials; Differential scanning calorimetry (DSC); Magnetic properties; Phase transitions; Thermodynamic properties